Structural Dynamics of Retroviral Genome and the Packaging - Miyazaki, Yasuyuki; Miyake, Ariko; Nomaguchi, Masako; Adachi, Akio (Frontiers in Microbiology, 2011)
Retroviruses can cause diseases such as AIDS, leukemia and tumors, but are also used as vectors for human gene therapy. All retroviruses, except foamy viruses, package two copies of unspliced genomic RNA into their progeny viruses. Understanding the molecular mechanisms of retroviral genome packaging will aid the design of new anti-retroviral drugs targeting the packaging process and improve the efficacy of retroviral vectors. Retroviral genomes have to be specifically recognized by the cognate nucleocapsid (NC) domain of the Gag polyprotein from among an excess of cellular and spliced viral mRNA. Extensive virological and structural studies have revealed how retroviral genomic RNA is selectively packaged into the viral particles. The genomic area responsible for the packaging is generally located in the 5’ untranslated region (5’ UTR), and contains dimerization site(s). Recent studies have shown that retroviral genome packaging is modulated by structural changes of RNA at the 5’ UTR accompanied by the dimerization. In this review, we focus on three representative retroviruses, Moloney murine leukemia virus (MoMLV), human immunodeficiency virus type 1 (HIV-1) and 2 (HIV-2), and describe the molecular mechanism of retroviral genome packaging.